2020
DOI: 10.3390/ijerph17207432
|View full text |Cite
|
Sign up to set email alerts
|

Factors Influencing the Settlement Intentions of Chinese Migrants in Cities: An Analysis of Air Quality and Higher Income Opportunity as Predictors

Abstract: With rapid urbanization, the air pollution issue is becoming an increasingly serious issue given that people are strongly swayed in their location choice to settle down in a growing urban area where most job opportunities have been created. This study investigated the influences of both air quality and income on the settlement intentions of Chinese migrants by using microlevel samples of the China Migrants Dynamic Survey (CMDS) data from 2017 and the annual average concentration of PM2.5 (particles with diamet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
13
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(16 citation statements)
references
References 58 publications
2
13
1
Order By: Relevance
“…Second, we found that the migrants often faced a trade-off between economic advantages and air quality in their settlement intention. This result is same as previous studies ( 2 ). In varying degrees, the economic advantage of the inflow cities would offset the negative effect of air pollution on the migrants' settlement, and the effect differs among different populations.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…Second, we found that the migrants often faced a trade-off between economic advantages and air quality in their settlement intention. This result is same as previous studies ( 2 ). In varying degrees, the economic advantage of the inflow cities would offset the negative effect of air pollution on the migrants' settlement, and the effect differs among different populations.…”
Section: Discussionsupporting
confidence: 93%
“…First, this study verifies the differences in the settlement intention among migrants from different groups. The study finds that female, married, minority, high age, non-farm hukou, and migrants with a closer mobility range are more willing to settle in the inflow cities, which is the same as the results of previous studies ( 2 , 27 ).…”
Section: Discussionsupporting
confidence: 87%
See 2 more Smart Citations
“…Although the migration of adult child may have serious implications on health status and health care utilization of older parents left behind, the possible health effects on older parents with chronic diseases left behind in China are still unclear. The aim of this study is to explore the effect of adult child’s migration on health status and health care utilization of older parents with chronic diseases left behind in the context of the urbanization in China [ 28 ]. In-depth research on these issues will provide the government with the information needed for policy-making.…”
Section: Introductionmentioning
confidence: 99%